H.266/VVC fast intra prediction using Sobel edge features - Yang, Shih‐Hsuan; Hsiao, Sheng‐Jung (Electronics letters, 2021)
Versatile video coding is the next‐generation video coding standard. Compared with the previous high efficiency video coding standard, versatile video coding reduces 30% or more bitrate but requires significantly higher encoding complexity. This Letter proposes a fast intra prediction algorithm for partition type selection and mode decision of versatile video coding. The Sobel operator is employed to extract the gradient intensity and edge direction of coding blocks. Early skip conditions for partition types are developed based on the dominant edge indicated by block gradients. The intra prediction modes are further restricted to the directions close to the edge orientation of a coding block. Experimental results indicate that the proposed method in the Intra‐only configuration saves 34.66% of the encoding time with a slight (0.61%) increase in Bjøntegaard delta bit rate, which achieves the best tradeoff between acceleration and quality among all the investigated methods.